Congenital Cutaneous Hemangioma Causing Cardiac Failure: A Case Report and Review of the Literature. Issue 6 (2nd October 2012) - Weitz, Nicole A.; Lauren, Christine T.; Starc, Thomas J.; Kandel, Jessica J.; Bateman, David A.; Morel, Kimberly D.; Meyers, Philip M.; Kadenhe‐Chiweshe, Angela; Wu, June K.; Garzon, Maria C.
Abstract We present a case of a large congenital hemangioma (CH) on the neck causing cardiac failure and thrombocytopenia in a female neonate. A trial of medical therapy with corticosteroids and propranolol was attempted, but the patient ultimately underwent definitive treatment with embolization and surgical resection with a positive outcome. A review of the English language literature revealed 16 previously reported cases of CHs complicated by congestive heart failure. This series supports known demographic features of CHs, including a lack of gender discrepancy and a predilection to affect the head and neck. These CHs are rarely diagnosed in utero; most patients present with a mass at birth. Cardiac failure is identified prenatally or in the first days of life. A mild to moderate thrombocytopenia and coagulopathy, which is likely transient and distinct from classic Kasabach‐Merritt phenomenon, accompanies many of these cases. There is a 30% associated mortality rate. Both medical and interventional treatment modalities have been reported. Steroids are the most commonly used medication, but without any clear benefit. We hypothesize that, based on its possible mechanisms of action, propranolol may be a more effective treatment for CHs requiring treatment. As surgical intervention may be necessary, we recommend a multidisciplinary approach to treating patients with problematic CHs.